(Keynote) Oxide based Resistive Memories for Low Power Embedded Applications and Neuromorphic Systems. (9th September 2015) - Vianello, Elisa; Garbin, Daniele; Jovanovic, Natalija; Bichler, Olivier; Thomas, Olivier; de Salvo, Barbara; Perniola, Luca
Abstract : Oxide based resistive memories (OxRAMs) is one of the potential candidates for non-volatile logic circuits and neuromorphic circuits in the applications of wearable devices, internet of things (IoT), cloud computing, and big-data processing. One of the main OxRAMs issue is the noise behavior of the high resistance state (HRS). In this work, we will demonstrate a hybrid (CMOS logic plus ReRAM devices) Non Volatile Flip Flop designed to face OxRAM variability. Concerning neuromorphic circuits, we will focus on the impact of resistance variability on the performance of Convolutional Neural Network (CNN) systems for visual pattern recognition applications.